Actualization Of Diversity In Religious Concepts: Comparison of Religious Culture in the Film Ranah Tiga Warna - Karim, Alifya Bussaina (Asketik: Jurnal Agama dan Perubahan Sosial, 2024)
This research is motivated by the diversity of religious concepts that are always visible in society. Diﬀerent communities will also be diﬀerent in expressing the religious values they adhere to. One thing that is visible is the diversity of religious concepts that occur in Indonesia, Jordan and Canada in the ﬁlm Ranah Tiga Warna. The phenomenon of diﬀerent religions was also revealed by Cliﬀord Geert when studying religion and culture in Indonesia and Morocco. Therefore, the author is interested in seeing further how the diversity of religious concepts is actualized in the ﬁlm Ranah Tiga Warna. The research uses a qualitative approach, with content analysis research methods (content analysis) after previously collecting data using documentation techniques, listening and taking notes. The research results found that there were diﬀerences in various expressions, including in behavior, religious symbols, and how to cover the private parts, especially for women.